The Impact Of Nanoparticles In Biomaterials Of Human Health - Rehman, Saira (Journal of Neonatal Surgery, 2025)
Background: The move towards incorporating nanoparticles into biomaterials systems is mainly due to their specific physicochemical features which make them useful in drug delivery, wound healing, and even tissue engineering. The worries surrounding their possible health risks such as toxicity, immune reactions, and bioaccumulation have raised attention from all sectors of society and science to intensify scrutiny. The perception and trust of society in the safety of nanoparticles in biomaterials need to be understood to enable focused risk communication, regulatory policies, and medical improvement. Objective : This study seeks to gauge the general public’s understanding and perceived benefits, health concerns, and degree of confidence in the safety of nanoparticles in biomaterials. The public perception of the use of nanotechnology in healthcare will be assessed using a quantitative survey approach to analyze the relationship and impact of the aforementioned factors on the public’s confidence. Methods : A descriptive cross-sectional study was developed using a survey administered to 250 subjects from various medical fields including professionals, engineers, and researchers, as well as total laymen. Participants were asked demographic questions and other questions about awareness, perceived benefits, health issues, and even their legislative opinions were collected through structured questionnaires. It was analyzed descriptively using central tendency and variability measures, relationships between variables via correlation analysis, regression modeling, reliability analysis, normality, and construct validity (Cronbach’s Alpha and Spearman-Brown tests). Shapiro-Wilk test was used for normality assessments. Results: The responses given did not follow a normal distribution which is suggestive of varying perceptions among participants. The reliability scale calculated was very low for Cronbach’s Alpha (0.185) and Spearman-Brown’s coefficient (0.33) which indicates a lack of internal reliability. The correlation analysis indicated weak to moderate correlations between perceived benefits, risks, and regulatory issues. Multiple regression analysis showed that all independent variables failed to significantly predict the respondent’s confidence in the safety of the nanoparticles. The R-squared values were low suggesting that other factors had more influence on public impression than was analyzed. Conclusion:This study analysis suggests that the public perception of the nanoparticles in biomaterials is vague and inconsistent making it difficult to communicate risks properly and provide a clearer education to the public regarding the regulation. The analysis shows that there is not much confidence among the public in the application of nanotechnology regardless of the benefits, risks, or regulations set but are influenced by media attendance and personal experiences. Further studies should improve the reliability of the survey, include more representative and larger samples, and investigate the issue with qualitative methods to understand better people’s attitudes towards nanotechnology in biomaterials